A Complementary Zakat–Waqf Integrated Model for Sustainable Economic Empowerment Programs - Muhammad, Adamu Abubakar; Afifi, Abdullah A (IDRIS Darulfunun Institute, 2025)
This paper develops a conceptual framework for integrating zakat and waqf as complementary instruments aimed at sustainable economic empowerment. The two main pillars of Islamic social finance, zakat and waqf, have historically and theologically pursued complementing social goals of the public interest (maslahah), social protection, and poverty alleviation. In many Muslim-majority nations, waqf (an endowment intended to produce enduring public benefit) and zakat (a redistributive, mandatory alms giving) have mainly functioned in separate institutional and legal frameworks while having a similar goal of improving human welfare and acts of worship. This paper aims to discuss the strategic integration of zakat and waqf, particularly in contemporary forms like cash waqf, zakat-funded waqf seed capital, and joint zakat-waqf impact programs, to significantly increase the resource base for programs aimed at sustainable economic empowerment, boost the effectiveness of attaining the Sustainable Development Goals (SDGs), and enhance governance and accountability in Islamic social finance. The paper presents an operational framework for integration, addresses governance safeguards and shariah considerations, and provides policy recommendations to practitioners, regulators, and donors using a systematic literature synthesis, comparative models, and illustrative case studies (Indonesia, Malaysia, Nigeria) and contemporary conceptual models. The study concludes that, despite operational, legal, and institutional obstacles, digitally enabled governance, standardized impact indicators, and hybrid public-private partnerships offer practical means to scale zakat-waqf integration for inclusive and sustainable development.